Formación de la trama urbana y transformaciones socioeconómicas recientes en la ciudad de Palma de Mallorca (1960-2001) - González Pérez, J. M. (Geographicalia, 2016)
The territorial consequences of the development and the intensification of the tourist phenomenon in the Balears Islands from the last half of the past century have affected the social and demographic composition of the main city of the Balearic system, Palma de Mallorca. In this paper, we investigate the present urban structure of Palma through its origins and its historical transformations. From this analysis we will, next, focus on the verification of the evolution in the inner city, as a consequence of the social and territorial changes of last half of XX century, as well as the present intra-urban behaviors aimed at recovering the inherited city.
Keywords: historical center; enlargement; inmigration; ageing; integral rehabilitation